The NLRP3 inflammasome as a new target in respiratory disorders treatment - Leszczyńska, Katarzyna; Jakubczyk, Dominika; Górska, Sabina (Frontiers in Immunology, 2022)
In recent years a continuous increase in new cases of respiratory disorders, such as rhinitis, asthma, and chronic obstructive pulmonary disease (COPD), has been observed. The exact pathomechanism of these diseases is still blurry, resulting in the lack of targeted and effective therapy. The conventional use of treatment strategies, such as antihistamine drugs and/or glucocorticosteroids act mainly symptomatically and have significant side effects. Specific allergen immunotherapy is only useful in the management of specific allergies and selected patients. Therefore, new therapeutic solutions are constantly being sought. The novelty of recent years has been the association between NLRP3 inflammasome activation and the development of airway inflammatory diseases. This seems to be an interesting therapeutic target that may support or even replace traditional therapies in the future. The review presented, discusses the contribution of NLRP3 inflammasome to the development of allergic rhinitis, allergic asthma, and COPD. Moreover, the modulatory properties of probiotics in the context of NLRP3 inflammasome are emphasised.